Remnants and ejecta of thermonuclear electron-capture supernovae: constraining oxygen-neon deflagrations in high-density white dwarfs - Jones, Samuel; Röpke, Friedrich (Astronomy and astrophysics, 2019)
The explosion mechanism of electron-capture supernovae (ECSNe) remains equivocal: it is not completely clear whether these events are implosions in which neutron stars are formed, or incomplete thermonuclear explosions that leave behind bound ONeFe white dwarf remnants. Furthermore, the frequency of occurrence of ECSNe is not known, though it has been estimated to be of the order of a few per cent of all core-collapse supernovae. We attempt to constrain the explosion mechanism (neutron-star-forming implosion or thermonuclear explosion) and the frequency of occurrence of ECSNe using nucleosynthesis simulations of the latter scenario, population synthesis, the solar abundance distribution, pre-solar meteoritic oxide grain isotopic ratio measurements and the white dwarf mass-radius relation. Tracer particles from the 3d hydrodynamic simulations were post-processed with a large nuclear reaction network in order to determine the complete compositional state of the bound ONeFe remnant and the ejecta, and population synthesis simulations were performed in order to estimate the ECSN rate with respect to the CCSN rate. The 3d deflagration simulations drastically overproduce the neutron-rich isotopes 48Ca, 50Ti, 54Cr , 60Fe and several of the Zn isotopes relative to their solar abundances. Using the solar abundance distribution as our constraint, we place an upper limit on the frequency of thermonuclear ECSNe as 1−3% the frequency at which core-collapse supernovae (FeCCSNe) occur. This is on par with or 1 dex lower than the estimates for ECSNe from single stars. The upper limit from the yields is also in relatively good agreement with the predictions from our population synthesis simulations. The 54Cr/52Cr and 50Ti/48Ti isotopic ratios in the ejecta are a near-perfect match with recent measurements of extreme pre-solar meteoritc oxide grains, and 53Cr/52Cr can also be matched if the ejecta condenses before mixing with the interstellar medium. The composition of the ejecta of our simulations implies that ECSNe, including accretion-induced collapse of oxygen-neon white dwarfs, could actually be partial thermonuclear explosions and not implosions that form neutron stars. There is still much work to do to improve the hydrodynamic simulations of such phenomena, but it is encouraging that our results are consistent with the predictions from stellar evolution modelling and population synthesis simulations, and can explain several key isotopic ratios in a sub-set of pre-solar oxide meteoritic grains. Theoretical mass-radius relations for the bound ONeFe WD remnants of these explosions are apparently consistent with several observational WD candidates. The composition of the remnants in our simulations can reproduce several, but not all, of the spectroscopically-determined elemental abundances from one such candidate WD.
Gesehen am 21.02.2019